Policy Brief Optimizing the First Thousand Days of Life (1000 HPK) Policy Program as an Effort to Prevent Stunting in Indonesia: Literature Review - Virgina Putri Sabila; Anita Rahmiwati; Nur Alam Fajar (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: 1000 HPK is a food insecure group which includes pregnant women, breastfeeding mothers and children under two years old. Thus, nutrition program policies are the focus of the 1000 HPK group in efforts to prevent stunting. Objective: The aim of this research was to carry out a literature review to determine the Policy Brief for Optimizing the First Thousand Days of Life (1000 HPK) Policy Program as an Effort to Prevent Stunting in Indonesia. Method: This research looked for journals used in the literature review, journals used in the literature review were obtained through international journal provider databases such as Google Scholar, PubMed, and Scince Direct. Researchers wrote appropriate keywords, namely 1000 HPK, stunting, and Policy Brief. Result: After conducting literature, the researcher obtained five articles that were relevant to the research topic, namely about 1000 HPK, stunting, and Policy Brief. Based on indicators, the 1000 HPK program has not yet reached the target in Indonesia, which is caused by the availability of human resources and infrastructure in implementing the 1000 HPK program at the Community Health Center which is still inadequate. Conclusion: Presidential Regulation number 42 of 2013 concerning the National Movement to Improve Nutrition was issued to support efforts to increase stakeholder participation and awareness in a planned and coordinated manner to accelerate nutritional improvements in the first 1000 days of life (1000 HPK) in efforts to accelerate nutritional improvements in the first 1000 days of life (1000 HPK) prevent stunting.